Effects of CrossFit training program and traditional gym training on morphological characteristics of men - Ljubiša Kićanović; Bogdan Živanović; Mila Vukadinović Jurišić; Jelena Obradović (Exercise and Quality of Life)
CrossFit is recognized as one of the fastest-growing high-intensity functional training modes in the world. The study aimed to compare the effects of the CrossFit training program and traditional gym training on anthropometric measurements in healthy, active men. The study sample consisted of 50 participants who were divided into two groups, 22 participants who practiced the CrossFit training program (CFT group; 28.64±2.04 years; body height 181.74±6.96 cm; body mass: 72.75±5.53 kg), and 28 participants who applied traditional gym training (GT group; 26.89±2.99 years; body height: 184.52±7.80 cm; body mass: 74.86±8.48 kg). A total of ten anthropometric measurements (Body height, Body mass, BMI, Subscapular, Abdominal and Triceps skinfolds, Chest, Forearm, Upper arm, and Thigh circumferences) were monitored before and after twelve weeks. The Shapiro-Wilk test was used to test the normality of distribution. The multivariate analysis covariance (MANCOVA) and analysis of covariance (ANCOVA) were used to analyze the data. The results of this study indicated that there were statistically significant differences between groups in the Circumference of the upper arm (p=0.02), Thigh circumference (p=0.00), Chest circumference (p=0.03), and Subscapular skinfold (p=0.00). The findings of this study demonstrated that healthy, active males who participated in the 12-week CrossFit training program improved their anthropometric measurements more than those who trained in the traditional gym training.